Potential intake of vitamins "A" and "D" through branded intravenous lipid emulsions: Liquid Chromatography-Tandem Mass Spectrometry Analysis. Issue 2 (April 2017) - Forchielli, Maria Luisa; Conti, Matteo; Patrono, Daniela; Mancini, Rita; Pession, Andrea; Puggioli, Cristina; Bersani, Germana
Summary: No data exist for vitamin A group and vitamin D2/D3 content in branded intravenous lipid emulsions (ILEs). Our goal is to evaluate and quantify their concentrations in different ILEs to assess whether they are clinically relevant. Analyses were carried out in triplicates on six ILEs: 1) 30% soybean oil-based, 2) 20% olive-soybean oil based, 3) 10 + 10% soybean - MCT coconut oil based, 4) 20% soybean-olive-MCT-fish oil based, 5) 20% soybean-MCT-fish oil based and 6) 10% pure fish oil based, respectively. Retinol group (vitamin A) and ergo-chole-calciferol (vitamin D2/D3) were analyzed and quantified by a quali-quantitative Liquid Chromatography-Tandem Mass Spectrometry (LC-MS/MS) method after potassium hydroxide alkaline hydrolysis, hexane extraction, reverse phase-liquid chromatography and specific multiple-reaction-monitoring (MRM) detection. On average, measured retinol content was in the range of 200–1000 μg/L in ILEs (1, 2, and 3), whereas it was higher (1000–2000 μg/L) in the ILEs containing fish-oil. Vitamin D content was in the range of 1–10 μg/L in the fish-oil based ILEs, but undetectable in those ILEs containing purely vegetable oils. This study shows that vitamin A and D contents are variably present in ILEs based on their different lipid sources. Both contents should be explicitly mentioned in the products.